1995
DOI: 10.1063/1.470420
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive torsional dynamics of malachite green molecules in solid matrices probed by fluorescence decay

Abstract: The torsional dynamics of phenyl rings of malachite green molecules in the excited state is studied in polymeric and monomeric glass matrices by measuring the fluorescence decay time as a function of temperature. It is shown that the phenyl rings rotate diffusively in solid polymers (polymethyl methacrylate and polyvinyl alcohol) quite rapidly even at low temperatures. To analyze the experimental results, we used the concept of microviscosity which controls the diffusive rotational motion of phenyl rings of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
1
37
1
Order By: Relevance
“…The fact that the nonradiative decay time of MG in the glassy samples is of Arrhenius-type temperature dependence is consistent with our previous studies. 33,34 Dhinojwala et al also found that below T g the rotational reorientation time of disperse red 1 in polystyrene shows an Arrhenius temperature dependence. 31 Below T g , the thermally activated hopping stops and molecules are frozen in a certain configuration so that they cannot move around.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The fact that the nonradiative decay time of MG in the glassy samples is of Arrhenius-type temperature dependence is consistent with our previous studies. 33,34 Dhinojwala et al also found that below T g the rotational reorientation time of disperse red 1 in polystyrene shows an Arrhenius temperature dependence. 31 Below T g , the thermally activated hopping stops and molecules are frozen in a certain configuration so that they cannot move around.…”
Section: Discussionmentioning
confidence: 93%
“…It is well known that the internal conversion at the sink is very fast for MG and the diffusive rotational motion is the rate-limiting process; then, the nonradiative decay time of MG is proportional to the microscopic viscosity of the surrounding solvent or host matrix molecules. 18,[32][33][34] Furthermore, since the internal potential for the phenyl-ring rotation is known to be barrierless and flat, and the required amount of rotation for the internal conversion to occur is very small, about 10°, 32 the dynamics of solvents in the supercooled state can be probed in the mesoscopic time window of 10 Ϫ11 -10 Ϫ8 s and on a length scale of several angstroms. 18 This feature is quite different from most of other molecular probes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 An increase in the quantum yield up to several orders of magnitude upon binding of this molecule to either BSA films, 14 specific antibody binding pockets 15 or suitable RNA structures 16,17 was reported in the literature. Particularly interesting appears the work by Kolpashchikov 18 where it was shown that a MGaptamers may be split in two and used as DNA sensors with single mismatch resolution.…”
mentioning
confidence: 95%